The Effectiveness of Comic as Learning Media to Enhance Knowledge of Menarche and Menstruation among Female Students in Yogyakarta - Annisa Nuraini; Sudarto Ronoatmodjo (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Menarche and menstruation are physiological process but they can cause physical, emotional discomfort, and anxiety. Menarche age tends to decline. Ignorance about menarche and menstruation may increase the risk of early pregnancy or unwanted pregnancy. This study aimed to determine the effectiveness of comic as a learning media to enhance knowledge on menarche and menstruation among female primary school students in Yogyakarta.Subjects and Method: This was a quasi-experiment with before and after study along with control group design conducted at Muhammadiyah primary schools in Sagan and Kauman, Yogyakarta, from October to November 2016. The sample of this study was 90 female students of primary school. The dependent variable was knowledge of menarche and menstruation. The independent variable was learning media (comic versus leaflet). The data were collected through questionnaire. The data were analyzed by Mann-Whitney test.Results: The increase in knowledge scores after intervention in the comic group (mean= 53.30) was higher than leaflet group (mean= 38.04), and it was statistically significant (p= 0.005).Conclusion: Comic is more effective as learning media than leaflet in enhancing knowledge of menarche and menstruation among primary school students.Keywords: menarche, menstruation, comic, leaflet, learning mediaCorrespondence: Annisa Nuraini. Faculty of Public Health, Universitas Indonesia, Jl. Prof. Dr. Sujudi, Pondok Cina, Beji, Depok, West Java. Email: aninisaa.nuraini@gmail.com. Mobile: 085758919474.Journal of Health Promotion and Behavior (2018), 3(4): 257-262https://doi.org/10.26911/thejhpb.2018.03.04.05